2021
DOI: 10.3390/toxins13040291
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Effects of Acute Ergot Exposure in Sheep

Abstract: Ergotism is a common and increasing problem in Saskatchewan’s livestock. Chronic exposure to low concentrations of ergot alkaloids is known to cause severe arterial vasoconstriction and gangrene through the activation of adrenergic and serotonergic receptors on vascular smooth muscles. The acute vascular effects of a single oral dose with high-level exposure to ergot alkaloids remain unknown and are examined in this study. This study had two main objectives; the first was to evaluate the role of α1-adrenergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Therefore, the effects of ergot alkaloids on mammalian systems such as humans and livestock (i.e., cattle, sheep, horses and goats) are diverse, where, in the case of livestock, observed symptomatic responses to ergot alkaloid exposure can be highly variable and, therefore, historically difficult to diagnose [38]. Gangrenous ergotism occurs most frequently from acute ergot alkaloid exposure, caused by general blood vessel vasoconstriction and dysfunction resulting in tissue necrosis (dry gangrene) of the extremities such as the ear tips, tail, lower limbs and hooves [37][38][39]. In other instances, the consumption of subtle quantities of-and the prolonged exposure of livestock to-ergot alkaloids negatively impacts energy metabolism, feed efficiency and livestock productivity, as evidenced by decreases in food intake, live weight gain, circulating prolactin, reproductive performance, milk production and hyperthermia [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effects of ergot alkaloids on mammalian systems such as humans and livestock (i.e., cattle, sheep, horses and goats) are diverse, where, in the case of livestock, observed symptomatic responses to ergot alkaloid exposure can be highly variable and, therefore, historically difficult to diagnose [38]. Gangrenous ergotism occurs most frequently from acute ergot alkaloid exposure, caused by general blood vessel vasoconstriction and dysfunction resulting in tissue necrosis (dry gangrene) of the extremities such as the ear tips, tail, lower limbs and hooves [37][38][39]. In other instances, the consumption of subtle quantities of-and the prolonged exposure of livestock to-ergot alkaloids negatively impacts energy metabolism, feed efficiency and livestock productivity, as evidenced by decreases in food intake, live weight gain, circulating prolactin, reproductive performance, milk production and hyperthermia [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Gangrenous ergotism occurs most frequently from acute ergot alkaloid exposure, caused by general blood vessel vasoconstriction and dysfunction resulting in tissue necrosis (dry gangrene) of the extremities such as the ear tips, tail, lower limbs and hooves [37][38][39]. In other instances, the consumption of subtle quantities of-and the prolonged exposure of livestock to-ergot alkaloids negatively impacts energy metabolism, feed efficiency and livestock productivity, as evidenced by decreases in food intake, live weight gain, circulating prolactin, reproductive performance, milk production and hyperthermia [37][38][39]. Pregnant and lactating animals are most susceptible to ergot alkaloid exposure due to increased risk of abortion and agalactia syndrome (the absence or failure to secrete milk); there is a direct correlation of ergopeptide exposure with a decrease in prolactin, growth hormone and luteinizing hormone secretion, and the inhibition of milk production [37].…”
Section: Discussionmentioning
confidence: 99%
“…A very specific pathology associated with ergot alkaloids and ergotism is a chronic vasoconstriction. Yonpaim et al [ 21 ] looked at the acute exposure of ergot alkaloids on vasoactivity in ovine vasculature, and Valente et al [ 22 ] evaluated prolonged ergot alkaloid exposure on the vasoactivity of bovine vasculature. Both studies [ 21 , 22 ] respectively evaluated aspects related to the ability of ergot alkaloids to interact with adrenergic and serotonergic receptors [ 23 ], and both papers concluded that receptor-mediated treatments for ergot alkaloid-induced vasoconstriction could be explored as potential therapies.…”
mentioning
confidence: 99%
“…Yonpaim et al [ 21 ] looked at the acute exposure of ergot alkaloids on vasoactivity in ovine vasculature, and Valente et al [ 22 ] evaluated prolonged ergot alkaloid exposure on the vasoactivity of bovine vasculature. Both studies [ 21 , 22 ] respectively evaluated aspects related to the ability of ergot alkaloids to interact with adrenergic and serotonergic receptors [ 23 ], and both papers concluded that receptor-mediated treatments for ergot alkaloid-induced vasoconstriction could be explored as potential therapies. From a systemic evaluation of ergot alkaloids’ impact on the whole animal or microbiome, to the study of a specific symptom, there is much yet to be learned about how ergot alkaloids disrupt mammalian physiology.…”
mentioning
confidence: 99%